Carotenoids from Marine Microalgae: A Valuable Natural Source for the Prevention of Chronic Diseases - Maria Filomena de Jesus Raposo; Alcina Maria Miranda Bernardo de Morais; Rui Manuel Santos Costa de Morais (Marine Drugs, 2015)
Epidemiological studies have shown a relation between antioxidants and the prevention of several chronic diseases. Microalgae are a potential novel source of bioactive molecules, including a wide range of different carotenoids that can be used as nutraceuticals, food supplements and novel food products. The objective of this review is (i) to update the research that has been carried out on the most known carotenoids produced by marine microalgae, including reporting on their high potentialities to produce other less known important compounds; (ii) to compile the work that has been done in order to establish some relationship between carotenoids and oxidative protection and treatment; (iii) to summarize the association of oxidative stress and the various reactive species including free radicals with several human diseases; and (iv) to provide evidence of the potential of carotenoids from marine microalgae to be used as therapeutics to treat or prevent these oxidative stress-related diseases.